Biodegradable Polymers for Biomedical Additive Manufacturing. (September 2020) - Puppi, Dario; Chiellini, Federica
Highlights: Medical devices fabricated by additive manufacturing are clinically employed A large body of literature deals with 3D printing of biodegradable polymers Consolidated biopolymers processing protocols have been adapted for bioprinting A wide range of approaches are available for polyesters additive manufacturing Novel natural and synthetic polymers are being implemented in 3D printing Abstract: The tremendous interest received by additive manufacturing (AM) within the biomedical community is a consequence of the great versatility offered in terms of processing approach, materials selection, and customization of the resulting device. In particular the unparalleled control over structural and compositional features at the macro- and microscale, as a result of the large design freedom and high reproducibility, is making AM the technology of election for the fabrication of biodegradable medical devices. This article is aimed at providing an update overview of scientific literature on biodegradable polymers for AM application in the biomedical field. The main AM techniques applied so far to biodegradable polymers are outlined by presenting relevant materials processing requirements. The different classes of biodegradable polymers investigated for AM (i.e., proteins, polysaccharides, aliphatic polyesters of either natural or synthetic origin, polyurethanes, as well as other synthetic polymers under AM implementation) are described by highlighting their source of extraction, chemical modification, or synthesis route, and their physical-chemical and processing properties in relationship to AM. Relevant literature on their AM processing for medical and pharmaceutical applications is accordingly reviewed. Graphical abstract: Image, graphical abstract